Studies on Platelets of Patients with Inherited Platelet Disorders Suggest that Collagen-Induced Fibrinogen Binding to Membrane Receptors Requires Secreted ADP but Not Released α-Granule Proteins - Legrand, Chantal; Nurden, Alan T (Thrombosis and Haemostasis, 1985)
Collagen induces a saturable 125I-fibrinogen binding to normal human platelets. A role for secreted ADP in this process is supported by studies on 2 patients with the Chédiak-Higashi syndrome. Both collagen-induced nucleotide release and 125I-fibrinogen binding were strongly reduced while ADP-induced fibrinogen binding was normal. Platelets from 2 patients with the gray platelet syndrome bound normal amounts of 125I-fibrinogen in the presence of ADP or collagen despite the severe reduction of secretable α-granule proteins. Binding did not occur to collagen-stimulated type I thrombasthenic platelets which lacked GPIIb-IIIa complexes but was detected in amounts which correlated with the residual concentrations of GPIIb-IIIa in the platelets of a patient with type II disease. Our results allow us to propose that collagen-induced fibrinogen binding to normal platelets requires the presence of GPIIb-IIIa complexes and secreted ADP but proceeds independently of α-granule release.
Keywords: Platelet aggregation; Fibrinogen; Collagen; Platelet secretion; Inherited platelet disorders